Acoustic metamaterials for sound absorption and insulation in buildings - Arjunan, Arun; Baroutaji, Ahmad; Robinson, John; Vance, Aaron; Arafat, Abul (Building and environment, 2024)
Despite the emergence of acoustic metamaterials with superior sound absorption and transmission loss, their adoption for building sound insulation has been limited. Sound insulation design in buildings is still informed by the acoustic performance of conventional materials, where the mass law contradicts light weighting when it comes to acoustic design. In any case buildings close to noisy environments such as motorways, railway lines and airports still suffer from significant low frequency noise pollution. Although the limited working bandwidth of acoustic metamaterials is a major issue limiting its application, combining meta-units that interact at various frequencies alongside multi-layer conventional solutions can deliver superior sound insulation in buildings. The review put forwards acoustic metamaterials, specifically emphasising superior sound absorption and transmission/insertion loss as critical properties for effective building sound insulation. The paper reveals a variety of acoustic metamaterials that can be adopted to compliment conventional sound insulation approaches for acoustically efficient building design. The performance of these metamaterials is then explained through their characteristic negative mass density, bulk modulus or repeating or locally resonating microstructure. The review is also extended to air transparent acoustic metamaterials that can be used for sound insulation of building ventilation. Lastly the prospects and challenges regarding the adoption of acoustic metamaterials in building insulation are also discussed. Overall, tuneable, and multifunctional acoustic metamaterials when thoughtfully integrated to building sound insulation can lead to significant acoustic comfort, space-saving and light-weighting.